Accurate prediction of quantitative traits with failed SNP calls in canola and maize - Weber, Sven E.; Chawla, Harmeet Singh; Ehrig, Lennard; Hickey, Lee T.; Frisch, Matthias; Snowdon, Rod J. (Frontiers in Plant Science, 2023)
In modern plant breeding, genomic selection is becoming the gold standard to select superior genotypes in large breeding populations that are only partially phenotyped. Many breeding programs commonly rely on single-nucleotide polymorphism (SNP) markers to capture genome wide data for selection candidates. For this purpose, SNP arrays with moderate to high marker density represent a robust and cost-effective tool to generate reproducible, easy-to-handle, high-throughput genotype data from largescale breeding populations. However, SNP arrays are prone to technical errors that lead to failed allele calls. To overcome this problem, failed calls are often imputed, based on the assumption that failed SNP calls are purely technical. However, this ignores biological causes for failed calls, for example deletions, and there is increasing evidence that gene presence-absence and other kinds of genome structural variants can play a role in phenotypic expression. Because deletions are frequently not in linkage disequilibrium with their flanking SNPs, permutation of missing SNP calls can potentially obscure valuable marker-trait associations. In this study, we analyze published datasets for canola and maize using four parametric and two machine learning models and demonstrate that failed allele calls in genomic prediction are highly predictive for important agronomic traits. We present two statistical pipelines, based on population structure and linkage disequilibrium, that enable the filtering of failed SNP calls that are likely caused by biological reasons. For population and trait examined, prediction accuracy based on these filtered failed allele calls was competitive to standard SNP based prediction, underlying the potential value of missing data in genomic predictions approaches. The combination of 2 This is a provisional file, not the final typeset article SNPs with all failed allele calls or the filtered allele calls did not outperform predictions with only SNPs based prediction due to redundancy in genomic relationship estimates.